2012
DOI: 10.1136/oemed-2011-100244
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat application and respiratory health effects among South Korean farmers

Abstract: Our findings suggest a possible association between paraquat application and adverse respiratory health effects among farmers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
5
28
0
1
Order By: Relevance
“…A study in Korean farm workers indicated an exposure-response relationship between the risk of restrictive ventilator defects and duration of paraquat application 32. This is comparable to our result of an exposure-response trend between cumulative exposure and risk of FEV 1 /FVC <0.8 though the effect seen in the high exposure group of our study is larger than that observed in the Korean study (ie, ORs of 8.48 and 1.89, respectively).…”
Section: Discussionsupporting
confidence: 82%
“…A study in Korean farm workers indicated an exposure-response relationship between the risk of restrictive ventilator defects and duration of paraquat application 32. This is comparable to our result of an exposure-response trend between cumulative exposure and risk of FEV 1 /FVC <0.8 though the effect seen in the high exposure group of our study is larger than that observed in the Korean study (ie, ORs of 8.48 and 1.89, respectively).…”
Section: Discussionsupporting
confidence: 82%
“…In particular, paraquat was the most used herbicide in South Korea in both frequency and volume and has been a major causative agent leading to acute poisoning death. 36 Related long-term health effects such as depressive symptoms 4 and restrictive ventilatory defects 6 have also been reported among farmers who applied paraquat in South Korea.…”
Section: Identification Of Hazardous Pesticidesmentioning
confidence: 98%
“…6 In particular, deaths and illness due to acute pesticide poisoning have posed a major public health problem in South Korea. 7,8 Despite extensive use of agricultural pesticides in South Korea and the gravity of their adverse health effects, little is known about the usage and trends of the agricultural pesticides applied.…”
Section: Agricultural Pesticide Usage and Prioritizationmentioning
confidence: 99%
“…Among pesticide applicators, several studies showed impairments in respiratory function, especially with paraquat (reduction associated with the number of years of application) [48] and organophosphate, carbamate, neonicotinoid insecticides and bipyridylium herbicides, sometimes with a dose-effect relationship [46].…”
Section: Discussionmentioning
confidence: 99%
“…Working in the agricultural sector was assumed to be equivalent to being exposed to pesticides. However, although only a few studies assessed lifelong pesticide use and calculated cumulative exposure indexes, they all found a dose-effect relationship [32,37,46,48]. Table 2 presents a summary of the longitudinal studies on respiratory health and occupational pesticide exposure.…”
Section: Studies On Agricultural Workersmentioning
confidence: 99%